Translation Shift Of Verbs And Verb Phrases On Married To The Viscount By Sabrina Jefries Into Rahasia Sang Viscount - Setyawati, Red Cea, Dra. Dwi Haryanti, M.Hum, Dr. Anam Sutopo, M.Hum (2013)
The aims of this research are to classify the types of verbs and verb phrases and to describe the equivalent translation in the novel Married to the Viscount by Sabrina Jefries into Rahasia Sang Viscount.This research is descriptive qualitative research. The data are in the forms of sentences containing verbs and verb phrases. They are collected from both of the novels by using documentation method. She applies comparative method for analyzing the collected data of the study. The results of the research show that first, there are 12 types translation shift of verbs and verb phrases. They are 1) 6 data or 3% belong to category shift containing verb which is translated into noun, 2) 4 data or 2% belong to category shift containing verb is translated into adverb, 3) 7 data or 3,5% belong to category shift containing to verb is translated into adjective, 4) 12 data or 6% belong to category shift containing lingking verb which is translated into adverb, 6) 4 data or 2% belong to category shift containing verb into particle -lah, 7) 10 data or 5% belong to category shift containing verb is not translated, 8) 52 data or 26% belong to verb which is translated into verb phrase, 9) 9 data or 4,5% belong to verb which is translated into adjective phrase, 10) 3 data or 1,5% belong to verb phrase which is translated into noun, 11) 78 data or 39% belong to verb phrase which is translated into verb, 12) 12 data or 6% belong to verb phrase which is translated into adjective, 3 data or 1,5% belong to verb phrase which is translated into adverb. Second, the researcher finds 198 data or 99% belong to equivalent translation while 2 data or 1% belong to non equivalence.